2013
DOI: 10.1097/tp.0b013e31828ee151
|View full text |Cite
|
Sign up to set email alerts
|

The Differential Tissue Expression of Inflammatory, Oxidative Stress, and Apoptosis Markers in Human Uncontrolled Non-Heart-Beating Donors

Abstract: The initial tissue damage generated during the UNHB donation process is at least comparable with that observed in BDD. However, although the expression of the immediate immune response and apoptosis markers is similar, a mild impairment of the local antioxidant activity was observed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The accumulation of acute and chronic injuries in the donor leads to increased senescence and reduced organ quality. In ECD donors, this may be due to an increase in age-related oxidative damage ( Figure 2 ) [ 16 ] as well as a reduction of autophagic activity and hence the inability to remove oxidatively damaged organelles. This link was shown in the kidneys of aged rats, where a high caloric diet exacerbated oxidative damage and aging, while autophagy was reduced [ 79 ].…”
Section: Autophagy and Oxidative Stress In Transplantationmentioning
confidence: 99%
See 1 more Smart Citation
“…The accumulation of acute and chronic injuries in the donor leads to increased senescence and reduced organ quality. In ECD donors, this may be due to an increase in age-related oxidative damage ( Figure 2 ) [ 16 ] as well as a reduction of autophagic activity and hence the inability to remove oxidatively damaged organelles. This link was shown in the kidneys of aged rats, where a high caloric diet exacerbated oxidative damage and aging, while autophagy was reduced [ 79 ].…”
Section: Autophagy and Oxidative Stress In Transplantationmentioning
confidence: 99%
“…Oxidative stress levels correlate with graft survival in all steps of the transplantation process including in the donor [ 6 16 ], during preservation [ 17 , 18 ], and reperfusion in the recipient. In donation after brain death (DBD) donors, brain death pathophysiology leads to increased renal oxidative damage markers which correlate with acute rejection, delayed graft function (DGF), and allograft function [ 6 16 ]. In donation after cardiac death (DCD) donors, cardiac arrest causes warm ischemia which is associated with impaired graft function and higher mortality rates [ 6 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the inevitable occurrence of WIP can activate the immune system in donors and aggravate I/R injury, which increases the risk of PGD. 10 In a rat model of LTx, we showed that 3% hydrogen gas ventilation during WIP improved post-transplantation lung function, as determined by improved partial pressure of arterial oxygen (PaO 2 )/fraction of inspired oxygen (FiO 2 ) ratio and static compliance of the lung grafts. Hydrogen preconditioning alleviated cardiac death lung graft I/R injury by reducing inflammatory mediator upregulation, demonstrated by decreased myeloperoxidase (MPO) activity, lower serum interleukin (IL)-6 and tumor necrosis factor (TNF)-a levels, and elevated IL-10 level.…”
Section: The Protective Effect Of Hydrogen On Donor Lung Injurymentioning
confidence: 97%
“…Uncontrolled DCD procedures involve extended periods of warm ischemia, intentionally amplifying cellular damage through inflammatory responses, oxidative stress, and apoptotic processes [28].…”
Section: Warm Ischemia Injury In Donation After Cardiac Deathmentioning
confidence: 99%